Sustainability knowledge, attitudes, and behaviors among healthcare professionals in Jordan - Allari, Rabia; Hamdan, Khaldoun; Alfasfos, Nedal; Zahran, Zainab; Al-Harazneh, Raghad (Frontiers in Sustainability, 2025)
BackgroundImproving quality, efficiency, and environmental responsibility in healthcare requires sustainability, a concept that is gaining increasing recognition. In low-and middle-income countries such as Jordan, however, little is known about how healthcare professionals perceive sustainability.AimThis study aimed to assess healthcare professionals’ perceived knowledge, attitudes, and behaviors regarding healthcare sustainability and the correlation between their perception and demographic characteristics in Jordan.MethodsA descriptive correlational design was utilized in this study. The validated Sustainability Consciousness Questionnaire (SCQ-S) was used to electronically gather data from 306 healthcare professionals employed by private hospitals in Amman, Al Zarqa, and Al Salt between January and May 2025. SPSS v 26 was used to conduct ANOVA tests and descriptive statistics.ResultsAbout 286 (93.5%) of participants scored higher than the midpoint of SCQ-S, indicating a high level of overall sustainability consciousness (M = 101.35, SD = 19.74). Environmental sustainability behaviors scored lowest (M = 10.77, SD = 2.71), while economic sustainability knowledge scored highest (M = 11.64, SD = 2.61). The ANOVA test revealed significant differences in HCP sustainability knowledge scores based on their specializations (F 3.61(3,302), p = 0.014). And based on their age (F = 4.07(3,302), p = 0.007). Older physicians and healthcare professionals scored higher than younger nursing staff (p < 0.05). Social media was the main source of information for more than half of the participants, 167 (54.6%), who were not familiar with the Sustainable Development Goals.ConclusionAlthough Jordanian healthcare professionals have a strong awareness of and positive attitudes toward sustainability, this is not always reflected in their behavior, particularly when it comes to environmental practices. To close this knowledge and behavior gap, health education must incorporate sustainability and sustainable development goals content in addition to institutional support and behavior empowerment.